Dipeptidyl nitroalkenes as potent reversible inhibitors of cysteine proteases rhodesain and cruzain - Latorre, Antonio; Schirmeister, Tanja; Kesselring, Jochen; Jung, Sascha; Johé, Patrick; Hellmich, Ute A.; Heilos, Anna; Engels, Bernd; Krauth-Siegel, Renate; Dirdjaja, Natalie; Bou-Iserte, Lledó; Rodríguez, Santiago; et al. (ACS medicinal chemistry letters, 2016)
Dipeptidyl nitroalkenes are potent reversible inhibitors of cysteine proteases. Inhibitor 11 resulted to be the most potent one with Ki values of 0.49 and 0.44 nM against rhodesain and cruzain, respectively. According to enzymatic dilution and dialysis experiments, as well as computational and NMR studies, dipeptidyl nitroalkenes are tightly binding covalent reversible inhibitors.